Biophysical Rangeland Resource Assessment in Isiolo, Baringo and Marsabit counties of Kenya - Lutta, Alphayo; Musembi, John (CGIAR System Organization, 2024)
The baseline survey conducted on plant species measurements in the selected rangeland management units of Baringo, Isiolo and Marsabit counties revealed evidence of degraded rangelands. The biophysical survey aimed to assess the current state of vegetation cover, species composition and ecosystem health in these critical ecosystems. The findings provide valuable insights into the extent of degradation and the urgent need for restoration efforts to ensure sustainable rangeland management and livelihoods for pastoral communities. The rangeland evaluation team found that significant portions of the pastoral rangelands are experiencing reduced vegetation cover, leading to increased bare ground and soil erosion. Overgrazing, climate change and land use changes were identified as the primary contributors to this decline.